2023
DOI: 10.1177/87560879231153702
|View full text |Cite
|
Sign up to set email alerts
|

Blown film stability for low, medium, and high molecular weight polylactic acid and their tensile properties

Abstract: Three poly (lactic acid) (PLA) resins with molecular weight (Mw) equal to 55 (3251D), 125 (L105) and 163 (LX175) kg/mol were characterized in terms of capillary viscosity, mechanical and thermal properties and used to produce blown films. The effect of temperature, extrusion rate, stretching (TUR) and blow-up (BUR) ratios were evaluated to determine the optimum processing conditions for blown films based on the bubble stability and to determine their final tensile properties. As expected, the processing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Weight loss due to thermal degradation was recorded in the 30–600°C range. PLA degradation occurs in a single step as reported for different PLA grades, 43 whereas TPS and the blends show multiple degradation stages due to their complex formulation.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Weight loss due to thermal degradation was recorded in the 30–600°C range. PLA degradation occurs in a single step as reported for different PLA grades, 43 whereas TPS and the blends show multiple degradation stages due to their complex formulation.…”
Section: Resultsmentioning
confidence: 76%
“…grades, 43 whereas TPS and the blends show multiple degradation stages due to their complex formulation. PLA was the most stable material with an initial degradation between 293 and 300 C and a maximum degradation rate (DTGA) at 372 C. For the blends, the first step occurs at 100-126 C corresponding to the loss of weakly bound water and low molecular weight compounds.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…These data correlate well with the values for switch overpressure recorded during the injection molding process, which varied from about 599–633 bar for the unprocessed materials (L105 and Opt series) to 492–539 for the extruded ones (SD and LD samples). The reduced viscosity of the polymer is an indication of its degradation; to minimize this effect, chain extenders, isocyanates, and other additives are being studied as a means to increase the recyclability of PLA products [ 9 , 33 ]. The start of the degradation can be observed in the yellowish color observed for the injection-molded samples, and is tabulated as yellow index in Section 3.9 .…”
Section: Resultsmentioning
confidence: 99%
“…However, these works were mainly focused on obtaining films and are not particularly aligned with blow molding or thermoforming, as they usually start from an extruded film rather than injection-molded samples. A recent study by Licea-Saucedo et al [ 33 ] included an analysis of blow-molding of different PLA grades, and found that temperature influences, to a great extent, the mechanical properties of the obtained films; instabilities were also encountered during the process. They found a high dependency between the temperature and the processability; the tensile strength of the films was independent of the stretching and blow-up ratios for PLA LX175, with an average value of 49 MPa.…”
Section: Introductionmentioning
confidence: 99%